Jurists and Political Authority in Ancient Rome: Array - Mehmeti, Sami (Acta Universitatis Danubius. Juridica, 2020)
The relationship between jurists and political authority has a profound importance in every society. This is especially true for Ancient Rome where law was related so directly to politics and jurists had significant influence in public life. This paper aims to give an insight on the evolution of the relations between Roman jurists and the political authorities. When the legal science emerged in the Late Republican period jurists enjoyed a considerable freedom and autonomy, then during the Early Pricipate emperors begun to restrict their autonomy through ius respondendi. In the Late Principate the majority of the leading jurists were governmental officials and the balance in relations between jurists and the politics shifted towards the later. During the Dominate jurists were anonymous and under the total control of the emperor. The treatment of the relation between Roman jurists and emperors through centuries usually reflects the political climate of the time, some favoring the freedom of jurists while others the sovereign authority of emperors.